Structure-Guided Modification of Heterocyclic Antagonists of the P2Y(14) Receptor - Yu, Jinha (J Med Chem, 2018)
The P2Y(14) receptor (P2Y(14)R) mediates inflammatory activity by activating neutrophil motility, but few classes of antagonists are known. We have explored the structure activity relationship of a 3-(4-phenyl- 1H-1,2,3-triazol-1-yl)-5-(aryl)benzoic acid antagonist scaffold, assisted by docking and molecular dynamics (MD) simulation at a P2Y(14)R homology model. A computational pipeline using the High Throughput MD Python environment guided the analogue design. Selection of candidates was based upon ligand-protein shape and complementarity and the persistence of ligand-protein interactions over time. Predictions of a favorable substitution of a 5-phenyl group with thiophene and an insertion of a three-methylene spacer between the 5-aromatic and alkyl amino moieties were largely consistent with empirical results. The substitution of a key carboxylate group on the core phenyl ring with tetrazole or truncation of the 5-aryl group reduced affinity. The most potent antagonists, using a fluorescent assay, were a primary 3-aminopropyl congener 20 (MRS4458) and phenyl p-carboxamide 30 (MRS4478).